Study on a W-band modified V-shaped microstrip meander-line traveling-wave tube - 沈飞 魏彦玉 许雄 段海荣 宫玉彬 王文祥 (Chinese physics B, 2012)
The study on a miniaturized, low-voltage, wide-bandwidth, high-efficiency modified V-shaped microstrip meander-line slow-wave structure is presented. This structure is evolved from the original U-shaped microstrip meander-line slow-wave structure, combining the advantages of a traditional microstrip and a rectangular helix. In this paper, simulations of the electromagnetic characteristics and the beam-wave interaction of this structure are carried out. Our study shows that when the design voltage and the current of a sheet electron beam are set to be 4700 V and 100 mA, respectively, this miniature millimeter-wave power amplifier is capable of delivering 160-W output power with a corresponding gain of 37.3 dB and a maximum interaction efficiency of 34% at 97 GHz.